2016
DOI: 10.15406/unoaj.2016.03.00109
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Clinical Characteristics and Outcome of Acute Kidney Injury in Intensive Care Units of Alexandria University Hospitals

Abstract: Background: Acute kidney injury (AKI) considered as a major public health problem that affects millions of patients worldwide and leads to decreased survival and increased progression of chronic kidney disease (CKD).Aim of study: Epidemiology, clinical characteristics and outcome of acute kidney injury in patients admitted to main Alexandria university hospitals over six months. Methods:All patients who were admitted to intensive care units (ICUs) at Alexandria University Hospitals were prospectively studied. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Ahmed et al [18] reported that the incidences of risk, injury, failure, loss, and endstage renal disease were 25.9%, 29.24%, 15.56%, 17.92%, and 11.32%, respectively, in all departments of a university hospital in Cairo. Shafie et al [19] reported that 24% of ICU-admitted patients were classified as at risk,28.2%, and 47.8% as failing at Alexandria University Hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Ahmed et al [18] reported that the incidences of risk, injury, failure, loss, and endstage renal disease were 25.9%, 29.24%, 15.56%, 17.92%, and 11.32%, respectively, in all departments of a university hospital in Cairo. Shafie et al [19] reported that 24% of ICU-admitted patients were classified as at risk,28.2%, and 47.8% as failing at Alexandria University Hospital.…”
Section: Discussionmentioning
confidence: 99%